Relative Frequencies and Patterns of Malignant Lymphoma in a Reference Centre in Khartoum, Sudan: A Descriptive Study Based on the WHO Classification of Lymphoid Neoplasms - Abdalhabib, Ezeldine K (Asian Pacific Journal of Cancer Care, 2020)
Background: The effective management and choice of appropriate treatment of lymphoma subtypes depend on an accurate diagnosis and differentiation, which require comprehensive haematology and pathology work. Methods: A total of 134 cases of malignant lymphoma, newly diagnosed between January 2017 to January 2020, were selected. For each patient’s samples, complete blood count, immunohistochemistry, and morphological evaluation were done. Results: Clinical data showed that 81 patients (60.4%) were males and 53 (39.6%) females. The age range was 4 to 80 years. NHL lymphoma comprised 87.3% of cases, while HL comprised 12.7% of cases. Diffuse large B cell lymphoma was the most prevalent NHL subtype, representing 39.3% of cases. Among HL subtypes, mixed cellularity was present in 41.2% of cases. B cell lymphoma constituted 93.2% of cases. All HL patients and 74.4% of NHL patients had anaemia. Conclusion: This is the first statistical report of malignant lymphoma patterns in Sudanese patients. These data suggest that malignant lymphoma in Sudanese patients is more frequent in males than females; its incidence increases with age. Further, B cell lymphoma is more common than T cell lymphoma. Diffuse large B cell lymphoma was the most frequent NHL subtype.